Evaluation of black soldier fly larvae meal as a functional feed ingredient in Atlantic salmon (Salmo salar) under farm-like conditions - Radhakrishnan, Gopika; Liland, Nina S.; Koch, Marianne Wethe; Lock, Erik-Jan; Philip, Antony Jesu Prabhu; Belghit, Ikram (Frontiers in Aquaculture, 2023)
Atlantic salmon (Salmo salar) were fed diets containing black soldier fly larvae (BSFL) meal at two inclusion levels for 13 months in open sea-cages. BSFL meal replaced plant-based ingredients and dietary insect meal inclusion levels were at 5% and 10%. A commercial salmon diet was fed as a control diet. Fish were reared from ~173 g to ~ 4 kg and were randomly distributed into nine open sea-cages with ~6000 salmon/cage (12×12 m2; 1900 m3). Fish from the sea-cages were sampled at two time points (mid and final samplings) to study the dietary effects of BSFL meal on the general health and welfare. Monthly assessments of sea-lice and gill score were conducted to evaluate the overall well-being of the salmon. The findings from the current study revealed that dietary inclusion of BSFL meal up to 10% did not have any significant effects in general growth, welfare or survival. However, significant positive response was observed in the general skin mucosal, hematological, and gene expression profiles of salmon. Notably, the group of salmon fed with 5% BSFL meal showed a significant decrease in plasma aspartate transaminase and alanine transaminase. Also, a significantly higher expression of interleukin1β in both skin and gill along with upregulation of matrix metallopeptidase9 and mucin18 in gill were observed in salmon fed BSFL at 5%, which aided in increased immune responses. Apart from that, this group had significantly higher mucus secretions, decreased cortisol response and increased number of erythrocytes. Furthermore, the delousing stress had a significant effect on the plasma cortisol, and these responses were independent of the dietary effect. Moreover, these immune responses behaved differently at different fish size and time points, acknowledging the influence of various factors in immune modulation. Overall, the findings from this study showed the effects of dietary BSFL meal to modulate the immune status of salmon. This study aims to fill the existing knowledge gaps regarding the impact of incorporating BSFL meal as a functional feed ingredient into the salmon diet on health and immune status replicating real farm conditions.